New fossil record of a Jurassic pterosaur from Neuquén Basin, Vaca Muerta Formation, Argentina - Codorniú Dominguez, Laura Susana (2013)
Discoveries of Jurassic pterosaurs in the Southern Hemisphere are extremely unusual. In Argentina, pterosaurs from the Upper Jurassic (Tithonian) have only been found in the Northwest of Patagonia (Neuquén Basin). These come from marine deposits and three specimens have been discovered up to the present. In this paper, we report a new finding from the Neuquén Basin. This material is identified as a tibiotarsus, which probably belonged to an osteologically adult individual and represents a new species of a pterodactyloid pterosaur of medium size. This discovery provides new evidence that at least two different species of pterodactyloid pterosaurs may have coexisted in Los Catutos Member, Vaca Muerta Formation, from the shallow marine deposits of the Neuquén Basin.